P409 Non-invasive predictors of maintaining remission in patients with moderately to severely active Ulcerative Colitis treated with tofacitinib who dose-reduced from tofacitinib 10 mg twice daily to 5 mg twice daily: 6-month data from the double-blind, randomised RIVETING study. (27th May 2021) - D'Haens, G R; Dubinsky, M C; Regueiro, M; Santana, G O; Torres, J; Kulisek, N; Gardiner, S; Mundayat, R; Paulissen, J; Lawendy, N; Su, C; Modesto, I; et al.
Abstract: Background: Tofacitinib is an oral, small molecule JAK inhibitor for the treatment of ulcerative colitis (UC). RIVETING (NCT03281304) is an ongoing, double-blind, randomised, parallel-group study designed to evaluate the efficacy and safety of dose reduction to tofacitinib 5 mg twice daily (BID) vs remaining on 10 mg BID in patients (pts) with UC in stable remission on tofacitinib 10 mg BID maintenance therapy. Eligible pts had received tofacitinib 10 mg BID for ≥2 consecutive years in an open-label, long-term extension study (NCT01470612), and had been in stable remission for ≥6 months and corticosteroid-free for ≥4 weeks prior to enrolment. 1 We aimed to determine if faecal calprotectin (FCP), C-reactive protein (CRP) or partial Mayo score (PMS) can be used as predictors of maintaining remission after dose reduction. Methods: Median FCP levels, median CRP levels and mean PMS at baseline (BL), Month 1 and Month 3 were analysed by efficacy endpoint status at Month 6 in pts who dose-reduced to tofacitinib 5 mg BID. The proportions of pts who achieved efficacy endpoints at Month 6 were analysed by stool frequency (SF) subscore, rectal bleeding (RB) subscore and modified PMS. Results: Seventy pts were randomised to receive tofacitinib 5 mg BID in RIVETING. For pts in modified Mayo score remission at Month 6, PMS was relatively stable over time, whereas PMS increased from BL to Month 1 and Month 3 in pts not in modified Mayo score remission at Month 6; mean change from BL at Month 3 was 0.1 vs 0.7, respectively (Table 1). This trend was also observed for other efficacy endpoints (Table 1). Median FCP levels did not change from BL to Month 3 in pts who achieved Month 6 efficacy endpoints, whereas median FCP levels increased from BL to Month 3 in pts who did not achieve Month 6 efficacy endpoints (except remission) (Table 1). For all efficacy endpoints, no trend was observed in median CRP levels over time in pts who did and did not achieve Month 6 efficacy endpoints (Table 1). A numerically higher proportion of pts with a SF subscore, RB subscore or modified PMS of 0 at Month 1 or Month 3 achieved efficacy endpoints at Month 6 compared with pts with respective subscores >0 (Table 2). Conclusion: These analyses suggest that in pts previously in stable remission, an increase in FCP levels at Month 3, or PMS as early as Month 1, may help predict loss of efficacy after dose-reduction from tofacitinib 10 mg BID to 5 mg BID. A SF subscore, RB subscore or modified PMS of 0 at either Month 1 or Month 3 could indicate the likelihood of maintaining efficacy with tofacitinib 5 mg BID at Month 6. These analyses are post hoc, exploratory and limited by the small sample size. Reference: Vermeire et al. J Crohns Colitis 2020;Epub ahead of print